“Space to space, time after time, in various phases of scripture”: Spatiotemporal Issues in the Study and Editing of Modern Literary Manuscripts - Natali, Ilaria (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In 1803, Goethe wrote to the composer Carl Friedrich Zelter that “one does not get to know nature and works of art when they are finished; they must be grasped as they develop, in order to understand them to some extent” (qtd. in Marholz 60, my trans.). Goethe’s “organicist” approach to artistic creation remained a quite exceptional stance at the time: a similar interest in the historical mode of art can be re-encountered only in 1846, when Edgar Allan Poe discussed the composition of his poem “The Raven.” Goethe’s and Poe’s remarks represent the first expressions of an orientation which would prevail in the following century and culminate in Paul Valéry’s poetics; the latter considered works of art merely “abandoned” and never finished (1497), thus questioning the authority of the published text.